2022
DOI: 10.1590/1519-6984.249971
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of stunting among preschool and school-going children in the flood-affected areas of Pakistan

Abstract: Stunting is a significant public health problem in low- and middle-income countries. This study assessed the prevalence of stunting and associated risk factors of stunting among preschool and school-going children in flood-affected areas of Pakistan. A cross-sectional study was conducted by visiting 656 households through multi-stage sampling. Respondent’s anthropometric measurements, socio-demographic information and sanitation facilities were explored. A logistic regression model was used to determine determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
1
6
1
3
Order By: Relevance
“…This study’s stunting rate was lower than the 27.1% found in the Asia–Pacific region in 2021 [ 29 ]. This prevalence is also lower than that of studies carried out in Thailand, Pakistan, Burkina Faso, Rwanda, Tanzania, and Ethiopia, which found 38%, 50.7%, 32.48%, 37.6%, 52.8%, 37.5%, 32.8% and 38%, respectively [ 14 , 16 , 30 , 31 , 32 , 33 , 34 , 35 ]. However, our results were superior to those of other studies conducted in Vietnam, Mali, Benin, Senegal, and China, which found 25%, 14.1%, 24.2%, 16.6%, and 20.7%, respectively [ 13 , 36 , 37 , 38 , 39 ].…”
Section: Discussioncontrasting
confidence: 66%
“…This study’s stunting rate was lower than the 27.1% found in the Asia–Pacific region in 2021 [ 29 ]. This prevalence is also lower than that of studies carried out in Thailand, Pakistan, Burkina Faso, Rwanda, Tanzania, and Ethiopia, which found 38%, 50.7%, 32.48%, 37.6%, 52.8%, 37.5%, 32.8% and 38%, respectively [ 14 , 16 , 30 , 31 , 32 , 33 , 34 , 35 ]. However, our results were superior to those of other studies conducted in Vietnam, Mali, Benin, Senegal, and China, which found 25%, 14.1%, 24.2%, 16.6%, and 20.7%, respectively [ 13 , 36 , 37 , 38 , 39 ].…”
Section: Discussioncontrasting
confidence: 66%
“…A study concludes that flood negatively impacts mid-class-based children under five leading to malnutrition [ 9 ]. Being consistent with the findings of previous study, another study reports that the prevalence of malnutrition (50.7%) was substantially higher in flood affected areas of Khyber Pakhtunkhwa among children under 5 years of age [ 10 ].…”
supporting
confidence: 90%
“…Sebagaimana penelitian di Rwanda 28 , ibu yang berusia 25-34 tahun berisiko tinggi memiliki balita stunting. Penelitian lain juga menunjukkan bahwa stunting lebih tinggi pada usia ibu yang lebih muda di Pakistan 29 , Amerika Serikat 30 , dan Tanzania 31 . Sementara ibu dengan kelompok usia 25-34 tahun 32 dan di atas 35 tahun 32,33 ditemukan lebih rendah memiliki balita stunting.…”
Section: Hasil Dan Pembahasanunclassified
“…Proporsi balita stunting sedikit lebih tinggi pada keluarga besar (Tabel 1). Keluarga besar lebih meningkatkan risiko terjadinya stunting 29,36,40,59 . Kelangkaan sumber daya seperti jumlah dan mutu pangan rendah 40,48,76 , persaingan mengakses makanan 40 , dan kurangnya pelayanan kesehatan lebih banyak ditemukan pada keluarga dengan jumlah anggota besar 48,75,76 .…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation